Monitoring Docker monitor your Docker containers and their apps using various native and third-party tools with the help of this exclusive guide! - McKendrick, Russ (Packt Publishing, 2015)
Monitor your Docker containers and their apps using various native and third-party tools with the help of this exclusive guide! About This Book Get the only book that covers multiple methods to monitoring Docker Containers -your one-stop solution to all your Docker monitoring needs Learn how to implement third-party tools such as Datalog, cAdvisor, and more with this example-rich, hands-on guide Learn how to efficiently monitor Docker containers and get an edge over other administrators while maintaining apps on these containers Who This Book Is For This book is for DevOps engineers and system administrators who manage Docker containers and want to better manage these containers using expert techniques and methods and better maintain applications built on Docker. What You Will Learn Discover the tools built into Docker to gain an insight into your containers' performance Augment Docker's built-in tools with modern tools such as cAdvisor from Google, SysDig by Draios, and Soundcloud's Prometheus Integrate the monitoring of your containers with more traditional monitoring solutions such as Zabbix Take advantage of the various SaaS offerings from third parties to move monitoring away from your local infrastructure and into the cloud Discover the various ways to ship your applications' logs from the container to a central logging service Get the most out of your application and resources with the right implementation of your monitoring method In Detail This book will show you how monitoring containers and keeping a keen eye on the working of applications helps improve the overall performance of the applications that run on Docker. With the increased adoption of Docker containers, the need to monitor which containers are running, what resources they are consuming, and how these factors affect the overall performance of the system has become the need of the moment. This book covers monitoring containers using Docker's native monitoring functions, various plugins, as well as third-party tools that help in monitoring. Well start with how to obtain detailed stats for active containers, resources consumed, and container behavior. We also show you how to use these stats to improve the overall performance of the system. Next, you will learn how to use SysDig to both view your containers performance metrics in real time and record sessions to query later. By the end of this book, you will have a complete knowledge of how to implement monitoring for your co...
Includes index. - Online resource; title from PDF title page (EBSCO, viewed March 16, 2018)
Keywords: Linux; Virtual computer systems; Computer software -- Development; Client/server computing; Systèmes virtuels (Informatique); Architecture client-serveur (Informatique); COMPUTERS / Operating Systems / Linux; COMPUTERS / Client-Server Computing; Computer software; Development